INDICATOR OF VULNERABILITY TO SEDIMENT CARRY-OVER INTEGRATED TO GIS AND SR - Arantes, Leticia Tondato [UNESP]; Santos, Arthur Pereira dos [UNESP]; Cunha e Silva, Darllan Collins da [UNESP]; Lourenco, Roberto Wagner [UNESP] (Univ Estado Rio Janeiro, 2024)
Soil erosion is one of the most serious environmental problems, with direct impacts on landscape degradation and the quality of life of local populations. This phenomenon is responsible for the loss of fertile soils, pollution of watercourses, and degradation of ecosystems, in addition to increasing the risk of natural disasters. The growing pressure on natural resources requires more effective management and the implementation of preservation measures, especially in permanent preservation areas (PPA), which play a key role in protecting water bodies and mitigating the effects of erosion. Thus, the objective is to develop an indicator called Sediment Transport Vulnerability Indicator (STVI) to assess the risk of sediment transport from erosive processes to the water bodies in the subbasins of the Sorocabu & ccedil;u River Basin (SRB), located in the state of S & atilde;o Paulo. The results showed that the SRB has an average soil loss value that places it in the low class, with the topographic factor (LS) being the most influential, as higher levels of soil loss are found in areas with higher slopes. Regarding the STVI, subbasin 8 resulted in the highest value (0.32), indicating it is the sub-basin with the highest risk of sediment transport to watercourses, justified by having the highest average soil loss value and the largest proportions of conflicting areas in the PPA, requiring greater attention. In contrast, sub-basin 9 resulted in the best value (0.13), as it has higher levels of preserved riparian vegetation. Finally, the data obtained in this study contribute to identifying the sub-basins most vulnerable to sediment transport, providing support for management agencies in establishing measures to preserve water resources.
Keywords: geoprocessing; geoenvironmental analysis; environmental analysis; geospatial analysis